A Rapid and Simple Manifold to Study Exchangeable Cations and Cation Exchange Capacity in 24 Soil Samples Simultaneously - Kloster, Nanci Soledad; Perez, Maria Micaela; Mazzaferro, Fernando (Taylor & Francis, 2021)
The outcomes of this work highlight the development and validation of a rapid and simple manifold for determination of exchangeable cations [calcium (Ca), magnesium (Mg), sodium (Na), and potassium (K)] and cation exchange capacity (CEC) in soil. First, the performance of the manifold was evaluated to determine the best conditions to use: filter assembly, volume and number of aliquots of extracting solution, and the use of vacuum. Second, the analytical performance was study from trueness and precision analysis. For that, soil samples with assigned values, an in house reference material and unknown soil samples, were used, comparing their results with those obtained using the classical extraction method (agitation, centrifugation, and filtration). The performance study showed that a filter system assembled with S&S Nº859 type filter paper, cotton, and plastic piece is better to the other studied options. Four aliquots of 10 mL extracting solution and a few seconds of vacuum between additions is recommended to achieve the best recovery. The extraction procedure proposed using the manifold demonstrated to be accurate, and so can effectively replace the classical method for the extraction of exchangeable cations and CEC in soils. Regarding simplicity, rapidity, and simultaneity, the manifold method could be the method of choice for extraction up to 24 samples. Moreover, the manifold method significantly reduces the laboratory supplies and instrument used in the extraction steps in the classical method, attaining better efficiency and reducing costs associated to this stage of the analysis.